PEMAHAMAN MAHASISWA TERHADAP BENTUK, PROSES, DAN PANDANGAN PENANGANAN KEKERASAN SEKSUAL DI KAMPUS - Nur Afni Khafsoh; Suhairi Suhairi (Marwah: Jurnal Perempuan, Agama dan Jender, 2021)
Campus should protect the entire academic community from sexual violence. Sexual violence cases are often not revealed due to various things such as stigmatization and legal uncertainty. Such as sexual violence on campus.This research uses a quantitative research methodology with a survey approach. This study intends to determine student understanding related to forms of sexual violence and knowledge about handling on campus and student satisfaction in seeing the results of handling sexual violence on their campus. The results show that many students understand the forms of sexual violence on campus. However, students do not know information about handling cases of sexual violence and institutions under campus that concentrate on handling cases of sexual violence. This understanding of students is important to involve students in the disclosure of cases of violence on campus and create a campus that is friendly and protected from sexual violence. Students do not understand sexual violence caused by the culture on campus that does not take sides with survivors in accordance with the theory of power relations and a feminist perspective.